Effect of heavy metal on production and productivity of underground vegetable crops - Ahmad, Zahoor; Hossain, Akbar; Aziz, Amir; Karabulut, Fadime (Elsevier, 2025)
Environmental pollution is rapidly booming worldwide. The soil contaminated with heavy metals (HMs) like lead Cr, Mn, Fe, Ni, Cu, Zn, Cd, Pb, and Hg has serious environmental problems since these metals are nonessential and toxic to plants and animals and have significant toxic effects on human health. Recently, due to various anthropogenic activities such as mining, industrialization, and agricultural activities like the application of pesticides, fungicides, and fertilizers, HMs have been released into the soil, water, and atmosphere. These released HMs enter the plant system through various physiological processes, and it affects the plants’ growth and development. The concentration of HMs in the environment varies due to various activities, and it becomes toxic when it reaches above the permissible limits. The possible introduction of these elements has contributed to the increasing occurrence of HMs in the ecosystem through their direct ingestion from contaminated soils, consumption of vegetables grown on the contaminated soils or drinking wastewater that has percolated through such soils. Vegetables are grown all over the world for human needs and are relished as nutritional supplements. Accumulation of HMs occurs only when the vegetable crops are cultivated in HMs-contaminated environment, and as a result, these HMs enter the food. Toxic HMs cause structural damage and deformation in their physiological and biochemical activities. HMs absorptions in vegetables and nutrition have contrary relationships that influence the various portions of vegetables (protein, fat, and carbohydrate). In many instances, the content of toxic metals in vegetables is much beyond permissible limits. Hazard quotient assessment in various studies has shown that consumption of these vegetables can be toxic to both adults and children. © 2025 Elsevier Inc. All rights are reserved.
Keywords: crop production; Heavy metals; human health; negative impacts; vegetables